2016
DOI: 10.7717/peerj.1864
|View full text |Cite
|
Sign up to set email alerts
|

Impaired emotion recognition is linked to alexithymia in heroin addicts

Abstract: Several investigations document altered emotion processing in opiate addiction. Nevertheless, the origin of this phenomenon remains unclear. Here we examined the role of alexithymia in the ability (i.e., number of errors—accuracy and reaction times—RTs) of thirty-one heroin addicts and thirty-one healthy controls to detect several affective expressions. Results show generally lower accuracy and higher RTs in the recognition of facial expressions of emotions for patients, compared to controls. The hierarchical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
3
30
0
Order By: Relevance
“…Results of the current study revealed that compared to healthy controls, the participants with SUDs spent more time attending to the various smile expressions when making judgments about the expressions. These results are similar to prior research studies that have examined response times in the judgment of emotional facial expressions of individuals with SUDs and have also found that they often require more time than their healthy counterparts (Craparo et al, 2016;Foisy et al, 2005;Foisy et al, 2007). The overall additional time required to categorize the emotional expressions may have been due to other factors, such as the slowed cognitive processing observed in mood disorders such as depression, as the results indicated that those with SUDs presented with significantly higher levels of depression than controls.…”
Section: Perceptual-attentional Processes: Viewing Timesupporting
confidence: 89%
“…Results of the current study revealed that compared to healthy controls, the participants with SUDs spent more time attending to the various smile expressions when making judgments about the expressions. These results are similar to prior research studies that have examined response times in the judgment of emotional facial expressions of individuals with SUDs and have also found that they often require more time than their healthy counterparts (Craparo et al, 2016;Foisy et al, 2005;Foisy et al, 2007). The overall additional time required to categorize the emotional expressions may have been due to other factors, such as the slowed cognitive processing observed in mood disorders such as depression, as the results indicated that those with SUDs presented with significantly higher levels of depression than controls.…”
Section: Perceptual-attentional Processes: Viewing Timesupporting
confidence: 89%
“…Patients on opioid maintenance also show impairments in recognizing emotions from video clips depicting displays of basic emotions (McDonald et al, ). One study has found a specific improvement in disgust expression recognition in methadone maintenance users compared to abstinent users (Martin et al, ), yet it is also possible that opioid dependency‐related impairments in expression recognition are mediated by emotion‐recognition‐impairing alexithymic traits in the substance abuse population (Craparo et al, ). Taken together, definite conclusions regarding the role of the opioid system in emotion recognition cannot be reached at this stage because there are only a limited number of studies on the effects of opioid agonists/antagonists on emotion recognition in healthy volunteers.…”
Section: Opioids and Emotion Recognitionmentioning
confidence: 99%
“…In fact, both adequate compliance and adherence prevent its relative outcomes leading to a lower risk of developing related complications (American Diabetes Association, 2018). Due to this, self-care could be considered as a suggestive index of patients' adaptation to diabetes, which may involve psychological adjustment to disease and its related emotional distress (Lapolla et al, 2012;Schmitt et al, 2014;Del Piccolo et al, 2015;Craparo et al, 2016;Settineri et al, 2019a,b;Knowles et al, 2020). Emotional distress could exist independently from such chronic disease, though considering the higher risk of mortality and morbidity due to diabetes, a psychological elaboration processing would be useful for the psychic integration of the chronic illness experience within patients' daily life (Whittemore et al, 2010;Castelnuovo et al, 2015;Van Houtum et al, 2015;Stanton and Hoyt, 2017;Di Giuseppe et al, 2018Savarese et al, 2018;Catalano et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%